2009
DOI: 10.1074/jbc.m802790200
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Acid β-Glucosidase 1 in the Salvage Pathway of Ceramide Formation

Abstract: In the present study, we examined whether acid ␤-glucosidase 1 (GBA1), which hydrolyzes glucosylceramide to form lysosomal ceramide, was involved in PKC-regulated formation of ceramide from recycled sphingosine. Glucosylceramide levels declined after treatment of MCF-7 cells with a potent PKC activator, phorbol 12-myristate 13-acetate (PMA). Silencing GBA1 by small interfering RNAs significantly attenuated acid glucocerebrosidase activity and decreased PMA-induced formation of ceramide by 50%. Silencing GBA1 b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
32
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 45 publications
1
32
0
Order By: Relevance
“…This relates to previous work from our laboratory, which showed that the novel isoform PKC␦ is required for ASM activation leading to ceramide accumulation (9). Moreover, ASM and GBA1 both contribute to PKC␦-dependent ceramide accumulation, which is predominantly C 16 -ceramide (8). However, unique biological roles for ASM-and GBA1-derived ceramide had not been defined in the same context.…”
Section: Regulation Of Il-6 By Pkc and Sphingolipid Metabolism-mentioning
confidence: 63%
See 3 more Smart Citations
“…This relates to previous work from our laboratory, which showed that the novel isoform PKC␦ is required for ASM activation leading to ceramide accumulation (9). Moreover, ASM and GBA1 both contribute to PKC␦-dependent ceramide accumulation, which is predominantly C 16 -ceramide (8). However, unique biological roles for ASM-and GBA1-derived ceramide had not been defined in the same context.…”
Section: Regulation Of Il-6 By Pkc and Sphingolipid Metabolism-mentioning
confidence: 63%
“…1B) (8). These findings raise the possibility of a novel paradigm that not only the specific identity of a bioactive sphingolipid is important, but the enzyme from which it is produced within a subcellular location may dictate its biologic function.…”
Section: Regulation Of Il-6 By Pkc and Sphingolipid Metabolism-mentioning
confidence: 94%
See 2 more Smart Citations
“…Although several mammalian SMases have been identified and characterized (5), neutral sphingomyelinase 2 (nSMase 2, SMPD3) and acid sphingomyelinase (aSMase, SMPD1) are the most extensively studied enzymes in regulated Cer generation (6). Recently, glucosylceramidase was also implicated in the regulated formation of ceramide in the salvage pathway (7,8).…”
mentioning
confidence: 99%